Efficacy of Topical Glucosamine in Oral Lichen Planus - Galala, Sara A.; El Din, Nevine H Kheir; Al Ashiry, Shahira; El-kammar, Hala; M. Elbakry, Asmaa; M. Ezzatt, Ola (Journal of Neonatal Surgery, 2025)
Lichen planus (LP) is a chronic, immune-mediated, inflammatory condition that can affect the skin, nails, and mucous membranes. Oral lichen planus (OLP) is the mucosal counterpart, presenting as white, reticular lesions (asymptomatic) or erythematous erosions (symptomatic) that can cause symptoms ranging from spontaneous soreness to severe pain interfering with eating, speech, swallowing, and patients' daily activities. Treatment strategies for OLP vary depending on the severity and extent of the lesions. Despite this, corticosteroids remain the cornerstone of management; various treatment modalities have also been introduced and used, particularly in refractory cases. Glucosamine (GlcN) is an amino sugar that plays a crucial role in the synthesis of essential components of cartilage and connective tissue. It has anti-inflammatory and immunomodulatory effects. This is a case of successful management of symptomatic OLP with GlcN as a promising treatment modality for OLP.